Mesopotamian medicine and magic: studies in honor of Markham J. Geller - Geller, Markham J.; Panayotov, Strahil V.; Vacín, Luděk; Trabich, Gene (Ancient magic and divination, 2018)
Intro -- ‎Contents -- ‎Preface -- ‎Markham J. Geller: An Appreciation -- ‎Bibliography of Markham J. Geller (Panayotov and Vacín) -- ‎Chapter 1. Vetitive and Prohibitive: An Observation (Abusch) -- ‎Chapter 2. Sons of Seth and the South Wind (Annus) -- ‎Chapter 3. An Old Babylonian Oil Omen Tablet from the British Museum (Anor) -- ‎Chapter 4. Disease and Healing in the Book of Tobit and in Mesopotamian Medicine (Attia) -- ‎Chapter 5. A Transtextual View on the "Underworld Vision of an Assyrian Prince" (Bach) -- ‎Chapter 6. The 34th Extract of the UGU Series from Babylon: An Edition of the Tablet BM 35512 (Bácskay) -- ‎Chapter 7. Budge's Syriac Book of Medicines after One Hundred Years: Problems and Prospects (Bhayro and Rudolf) -- ‎Chapter 8. An Old Babylonian List of Sheep Body Parts (BM 29663) (Cohen) -- ‎Chapter 9. Putting Theory into Practice: Kiṣir-Aššur's Expertise between Textual Knowledge and Practical Experimentation (Couto-Ferreira) -- ‎Chapter 10. A Brief Look Eastward (Choukassizian Eypper) -- ‎Chapter 11. Two Old Babylonian Incantation Tablets, Purportedly from Adab (A 633 and A 704) (Farber) -- ‎Chapter 12. Of tirku, Moles and Other Spots on the Skin according to the Physiognomic Omens (Fincke) -- ‎Chapter 13. Amulets against Fever (Finkel) -- ‎Chapter 14. A Tale of Two Lands and Two Thousand Years: The Origins of Pazuzu (Frahm) -- ‎Chapter 15. Hermeneutics and Magic in the Commentary to Marduk's Address to the Demons (Gabbay) -- ‎Chapter 16. A New Medical Therapeutic Text on Rectal Disease (Heeßel) -- ‎Chapter 17. Mesopotamian Magic in Text and Performance (Mirelman) -- ‎Chapter 18. Divine Privilege of the Rich and Powerful? Seeking Healing of Illness by Presenting a Luxurious Gift (Oshima and Van Buylaere) -- ‎Chapter 19. BM 32339+32407+32645: New Evidence for Late Babylonian Astrology (Ossendrijver)